A Learning Model of Environmental Education to Enhance Environmental Ethics Behavior for Undergraduate Students in a University - et. al., Saowapong Yamaphat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
the purpose of this research was to develop a learning model of environmental education to enhance the environmental ethics behavior of undergraduate students in a university. A qualitative research design was employed 3 steps; firstly, the documentary review was used for investigating the theoretical definition of environmental ethics behavior. Then, an in-depth interview was used to keep a practical definition. Lastly, a focus group discussion was employed to confirm the component of a learning model. Data were collected by 20 experts for interviewing and 8 experts for focus group discussions, using a semi-structured interview, discussion recording form, and were analyzed together by content analysis and analytic induction later. The research findings revealed that 1) the environmental ethics behavior comprised of 4 characteristics. Those were: (1) Right conception as a basic understanding of the environmental issues or nature of reality (2) Right consumption was claimed to use the natural resources as long as needed and efficient use of resources (3) Right conservation was referred to the appropriate preservation, protection, and management of the environment and natural resources. (4) Right conduction was expanded the three previous characteristics for our sufficiency economy living and well-being. 2) A learning model of environmental education to enhance environmental ethics behavior of the undergraduate students in a university was a process model namely SWU-E. Those were (1) Starting (S), it is the openness of mind for receiving new situation and preparing for learning. (2) World viewing (W), as the evaluation of the value of the environment to create realistic opinions and a new perspective of their own. (3) Utilizing (U), applies a new perspective to create a balance of life with the environment. (4) Evaluating (E), assessing the value which is generated by their practice with the environment from a new perspective and keep improving. Interestingly, SWU-E model was proposed for cultivating the environmental ethics behavior of undergraduate students who are the next generation people to save our planet